Praca z sesji tematycznychImiquimod for the treatment of actinic keratosis - Michajłowski, Igor; Włodarkiewicz, Adam; Sobjanek, Michał; Placek, Waldemar (Dermatology Review/Przegląd Dermatologiczny, 2009)
Imiquimod (IM) is an agonist of Toll-like receptors and stimulates an innate and acquired immune response by induction of synthesis and release of many cytokines. It shows indirect antiviral and antineoplastic action and causes cell destruction by means of apoptosis. Numerous studies have proved the efficacy of IM in the treatment of precancerous lesions and in situ cancers of skin and mucosa. The article presents the current knowledge on the treatment of the most frequent precancerous condition, actinic keratosis, with the use of IM. Very good cosmetic effect seems to be a particular advantage of IM therapy. Treatment of the whole area of photodamaged skin (also subclinical lesions) determines better long-term therapeutic effect.